2014
DOI: 10.1007/s00256-013-1812-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual-energy CT in vertebral compression fractures: performance of visual and quantitative analysis for bone marrow edema demonstration with comparison to MRI

Abstract: VNC DECT images allowed an accurate demonstration of trauma-related abnormal attenuation in VCF, revealing the acute nature of the fracture, on both visual and quantitative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 31 publications
3
55
3
2
Order By: Relevance
“…The two false-positive findings occurred in young patients and were evaluated as red bone marrow areas in the vertebral bodies, as noted in a previous study. 1 The results are compatible with previous studies related to the assessment of bone marrow in spine trauma. 1,5 The sensitivity, specificity and predictive values for the assessment of vertebral oedema obtained in our study were similar to the values obtained in the studies of Wang et al and Bierry et al The assessment of both DSCT images and non-calcium images for oedema, knowledge regarding fracture classification and sclerotic changes may affect these sensitivity values.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The two false-positive findings occurred in young patients and were evaluated as red bone marrow areas in the vertebral bodies, as noted in a previous study. 1 The results are compatible with previous studies related to the assessment of bone marrow in spine trauma. 1,5 The sensitivity, specificity and predictive values for the assessment of vertebral oedema obtained in our study were similar to the values obtained in the studies of Wang et al and Bierry et al The assessment of both DSCT images and non-calcium images for oedema, knowledge regarding fracture classification and sclerotic changes may affect these sensitivity values.…”
Section: Discussionsupporting
confidence: 82%
“…Currently, only a few studies have reported on the use of DSCT to visualize the bone marrow. 1,5,11,23,29 The attenuation values measured on the non-calcium images obtained by DSCT were higher in abnormal bone marrow areas than in normal areas. These increased attenuation values are correlated with the knowledge about the increase in fluid and/or blood components of the bone marrow in trauma patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) for potentially enhanced visualization of areas with low BMD which may improve preoperative planning of transpedicular screw fixation. DECT may also be beneficial for preoperative imaging of the lumbar spine as it allows for depiction of bone marrow oedema in vertebral compression fractures [31,32].…”
Section: Discussionmentioning
confidence: 99%